Circulating miR-134 in mesial temporal lobe epilepsy: implications in hippocampal sclerosis development and drug resistance - Guerra Leal, Bárbara; Carvalho, Cláudia; Santos, Cristina; Samões, Raquel; Martins-Ferreira, Ricardo; Teixeira, Catarina; Rodrigues, Diana; Freitas, Joel; Lemos, Carolina; Chorão, Rui; Ramalheira, João; Lopes, João; et al. (Frontiers in Molecular Neuroscience, 2024)
AimmiR-134 has been widely reported as upregulated in experimental and human studies of Mesial Temporal Lobe Epilepsy the most common drug-resistant epilepsy (DRE). Studies have shown that the use of antagomirs, anti-miR-134, may be a promising therapeutic approach to these epilepsies. However, data on miR-134 in other epileptic syndromes is scarce. In this study, we aimed to quantify serum levels of miR-134 in a cohort of patients with Mesial Temporal Lobe Epilepsy-Hippocampal Sclerosis (MTLE-HS) and with Genetic Generalized Epilepsies (GGE). Additionally, we explored the correlation between miR-134 serum levels and clinical parameters, such as age at onset or febrile seizures antecedents, to evaluate its potential as a biomarker and therapeutic target in epilepsy.MethodsmiR-134 levels were evaluated in cell-free serum of 131 patients with epilepsy (75 women, 56 men; age 41.10 ± 13.12 years; 72 with DRE) and 42 healthy individuals (25 women, 17 men; age 42.40 ± 9.80 years). The epilepsy cohort included 77 MTLE-HS patients and 54 GGE patients.ResultsPatients with elevated miR-134 circulating levels were at higher risk of drug-resistant epilepsy (OR [95% CI] = 2.246 [1.111–4.539], p = 0.021). Other risk factors included an older age (OR [95% CI] = 1.032 [1.004–1.061], p = 0.025), history of febrile seizures (OR [95% CI] = 2.994 [1.385–6.471], p = 0.005) and higher disease duration (OR [95% CI] = 1.038 [1.011–1.066], p = 0.006). The strongest predictor of DRE was hippocampal sclerosis (OR [95% CI] = 10.338 [4.566–23.404], p < 0.001). Circulating miR-134 levels were significantly higher in MTLE-HS patients compared to controls (p < 0.05) and GGE patients (p < 0.05). However, the clinical utility of miR-134 in discriminating MTLE-HS patients from controls was only moderated (AUC = 0.651 ± 0.051 95% CI 0.551–0.751, p = 0.007).ConclusionWe show that miR-134 circulating levels are associated with DRE, especially in MTLE-HS, a syndrome characterized by severe hippocampal damage, consistent with activity-regulated miR-134 expression. This overexpression likely contributes to disease progression and our results support the potential of targeting miR-134 as a novel therapeutic approach for refractory epilepsy.